Poster 264: Ambulatory Surgery Centers Reduce Day-of-Surgery Expenditures for Anterior Cruciate Ligament Reconstruction Without Increasing Patient Out-of-Pocket Expenditure: A Breakdown and Comparison of Expenditures on 34, 862 Patients. Issue 7 (30th July 2022) - Carbone, Andrew; Wang, Kevin; Chu, Brennan; Darden, Christon; Shrestha, Nancy; Colvin, Alexis; Anthony, Shawn; Gladstone, James; Tiao, Justin
Objectives: Anterior cruciate ligament reconstruction (ACLR) is one of the most performed orthopedic procedures in the United States and the volume and cost are increasing annually. Patients are increasingly expected to share a larger economic burden with out-of-pocket expenditures. Recently, there has been a shift to perform more ACLR surgeries outside of the hospital setting to reduce costs. The purpose of this project is to understand the differences in costs between ACLR performed in ambulatory surgery center (ASC) versus outpatient hospital settings and if or how this affects the patient's out-of-pocket expenditure. Methods: We identified patients who had undergone outpatient arthroscopic ACLR in the United States (U.S.) using the IBM MarketScan Commercial Claims and Encounters Database. The database was chosen for its large, national sample of privately insured patients. Patients who had Current Procedural Terminology (CPT) code 29888 between April 1, 2013 and June 30, 2017 were included. Revision ACL procedures and procedures with a concomitant microfracture, medial collateral ligament, lateral collateral ligament, or posterior cruciate ligament repair or reconstruction (CPT: 29879, 27405, 27409, 27427, 29889) were excluded. Day-of-surgery expenditure was identified by summing all claims billed with an "immediate-procedure-related code" in a 3-day window surrounding the date of the procedure (Procedure Date ± 1 Day). The day-of-surgery expenditure was broken down into implant, anesthesia services, regional anesthesia, operating room facility, surgical team, and other expenditures. Regional anesthesia is not included in anesthesia services expenditure. Median and interquartile range were calculated for each variable. The breakdown of day-of-surgery expenditure and patient out-of-pocket expenditure between the outpatient hospital and ASC settings were compared using two-tailed Mann Whitney U Tests. Spearman Rank Order Correlation was done for all variables to test for association between expenditure and year to determine trends over time. All values were inflation adjusted to 2017 dollars. Results: A total of 34, 862 patients were identified. Our results indicated that ACLR performed in the outpatient hospital setting result in 60% greater day-of-surgery expenditure (p < 0.001) than in the ASC setting. In the outpatient hospital setting, operating room facility cost was 36% greater (p <0.001), anesthesia services was 7.1% greater (p<0.001), implant was 28% greater (p<0.001), but regional anesthesia was 22% lower (p<0.001). Additionally, for ACLRs performed in the outpatient hospital setting, Spearman coefficients demonstrated that expenditure for anesthesia services decreased (rho = -0.037, p < 0.001) and operating room facility cost increased (rho = 0.058, p < 0.001) over our study period. For ACLRs performed in the ASC setting, expenditure for regional anesthesia decreased (rho = -0.039, p < 0.001). Surgical team reimbursement decreased over time for ACLRs performed in both the ASC (rho = -0.156, p < 0.001) and outpatient hospital (rho = -0.11, p < 0.001) settings. Lastly, total patient out-of-pocket expenditure for ACLRs performed in the outpatient hospital setting vs. ASC setting was very similar though statistically different (p = 0.02, <10 difference). Conclusions: ACLR performed in an ASC setting results in significant cost savings for payers with no change in surgeon reimbursement. Most of the cost savings came from operating room facility expenditure. For patients, there is almost no financial difference regarding where the ACLR was performed, with the difference in patient out-of-pocket expenditure being less than 10. For the surgeon, surgical team reimbursements are essentially neutral between the ASC and outpatient hospital settings. However, the overall trend in surgical team reimbursement is downwards in both the ASC and outpatient hospital settings. For the two biggest stakeholders in the surgery (surgeon and patient), there are no financial incentives to do an ACLR at an outpatient hospital over an ASC. For a healthcare system, especially under a population health perspective, the incentive to perform ACLRs at an ASC is significant. The cost savings come from every breakdown category, with implant and operating room facility costs being significantly decreased in the ASC setting. Decreased implant costs were likely due to preferred vendor contracts for ASCs. The cost savings achieved per ACLR in an ASC vs. an outpatient hospital equals almost 6000. With nearly 100, 000 ACLRs performed per year, the U.S. healthcare system could save a projected 600 million per year on ACLRs alone when the surgery is performed in an ASC. Thus, our study shows that there is a clear financial advantage to the healthcare system for ACLRs being done at ASCs, although the patient does not realize these cost savings. Figure 1. Breakdown of Day-of-Surgery Costs by Location procedure performed: ASC vs Outpatient HospitaL ASC and Outpatient Hospitals were identified using the "Place of Service" variable. The figure details expenditure for breakdown categories that were identified in >50% of cases. Categories that were coded on less than 50% of cases were excluded. The "other" category includes excluded cases and claims that were not able to be classified. * indicates statistical significance done using Mann Whitney U Test with p <0.001. Day-of-surgery expenditure was lower for ACLRs performed in the ASC setting, but surgical team reimbursement was essentially equivalent between the two settings. Table 1. Patient out-of-pocket expenditure for ACLR performed iu ASC vs. Outpatient Hospital. Over the study period, there were more ACLRs performed in the outpatient hospital setting vs. ASC, but there is no financial incentive for the patient to have their ACLR done at an outpatient hospital. Mann Whitney U analysis showed a statistically significant difference (p = 0.023), but the difference was <10. Table 2. Breakdown of day-of-surgery expenditure between ASC and outpatient hospital settings; Spearman rho correlation coefficient between year and breakdown category and p-value. This table shows the trends over time in the breakdown categories for ACLRs perforined in both the ASC and outpatient hospital setting. For ACLRs performed in the ASC setting, regional anesthesia costs decreased over time. In the outpatient hospital setting, anesthesia services costs decreased while operating room facility costs increased over time. In both the ASC and outpatient hospital settings, surgical team reimbursement decreased indicating an overall decline over time. Table 1. Cumulative fixation technique ranking by biomechanical outcome. Surface Under the Cumulative Ranking (SUCRA) for each outcome by fixation technique.